Perancangan Web Blogger untuk Meningkatkan Branding UMKM Pondok Buah Uly - Dwi Laras Sakti Afrita; Fatimah Azahra; Novadilastri Novadilastri; Sularno Sularno (CV. ITTC INDONESIA, 2025)
MSMEs in Indonesia play an important role in supporting the national economy. However, not all MSMEs have access to and knowledge of how to utilize digital technology as a means of business development. One solution that can be used is a free blogging platform such as Blogger. Through blogging, business owners can introduce their products more widely and build a positive brand image. This study aims to design and implement a Blogger-based website for Pondok Buah Uly SMEs, with a primary focus on improving branding and market reach. The methodology used is a qualitative approach through direct interviews and observation. The results of this study indicate that blogs are very helpful for SMEs in presenting their business identity in a more professional manner, while also serving as a cheap and effective marketing medium.